Banking Digitalization and Operational Efficiency: A Qualitative Study on the Implementation of Paperless Systems in Sustainable Islamic Banking - Karin Aribi Ivanka; Nurlaila; Tuti Anggraini (FEBI IAIN Langsa, 2026)
This study aims to analyze the implementation of paperless systems in improving operational efficiency within sustainable Islamic banking in Indonesia through a Systematic Literature Review (SLR). The study is motivated by the increasing digital transformation of Islamic banking, while many institutions continue to rely on hybrid administrative systems that combine digital and paper-based documents, resulting in duplicated processes, higher operational costs, and reduced efficiency. Previous studies have primarily focused on customer-oriented digital services, whereas comprehensive discussions on paperless implementation in internal operations remain limited. The novelty of this study lies in integrating paperless systems, operational efficiency, green banking, sustainability, and Sharia governance into a unified analytical framework. The research employed a qualitative SLR approach by reviewing 30 journal articles published between 2022 and 2026 from multiple databases, including Scopus, Web of Science, ScienceDirect, Emerald, SpringerLink, Dimensions, Crossref, Google Scholar, Garuda, and SINTA. The findings indicate that paperless implementation improves administrative efficiency, reduces operational costs, enhances productivity, strengthens transparency and data security, and supports green banking practices. However, successful implementation depends on organizational capability, digital competence, technological readiness, cybersecurity, regulatory support, and management commitment. This study contributes theoretically by extending digital transformation literature in Islamic banking and provides practical recommendations for strengthening sustainable and Sharia-compliant digital governance.